2021
DOI: 10.3390/foods10122919
|View full text |Cite
|
Sign up to set email alerts
|

High–Pressure Processing vs. Thermal Treatment: Effect on the Stability of Polyphenols in Strawberry and Apple Products

Abstract: Polyphenols are important bioactive compounds that are affected by processing. The consumer’s demand for minimally processed products contributes to the increase in non-thermal technologies such as high-pressure processing (HPP) in the food industry. This review is aimed at critically discussing the positive and negative effects of thermal treatment (TT) and HPP on the stability of different polyphenol families in agro-food products obtained from strawberry and apple, two of the most used fruits in food proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 89 publications
(255 reference statements)
2
28
0
Order By: Relevance
“…well as processing and storage conditions of the product (Aaby et al, 2012;Mahmood et Arfaoui, 2021;Salazar-Orbea et al, 2021). All aforementioned factors could have been affected the total content of polyphenols in yogurts from this study.…”
Section: Total Polyphenols and Antioxidant Activity In Fruit Yogurts ...mentioning
confidence: 90%
“…well as processing and storage conditions of the product (Aaby et al, 2012;Mahmood et Arfaoui, 2021;Salazar-Orbea et al, 2021). All aforementioned factors could have been affected the total content of polyphenols in yogurts from this study.…”
Section: Total Polyphenols and Antioxidant Activity In Fruit Yogurts ...mentioning
confidence: 90%
“…Some traditional unit operations used in the fruit industry include peeling, chopping, crushing, sieving, and thermal treatments [ 2 ]. Many studies have determined how different processing techniques and conditions affect some sensitive nutrients (e.g., vitamins) and bioactive compounds, as well as the quality characteristics of fruit products [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in light of an increasing demand of consumers towards minimally processed and healthier products [ 5 ], non-thermal technologies such as high-pressure processing (HPP), cold atmospheric plasma, and pulsed electric fields, among others, have been developed [ 6 ]. It has been shown that the degree of processing in thermal and non-thermal processing techniques affects the stability of polyphenols in fruit products [ 3 ]. However, the degree of processing has not been fully assessed yet, as many authors categorize the degree of processing according to the number of ingredients in a food product or to the extent and purpose of food processing, and not based on the process itself [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five original papers have been published in this Special Issue which address the third topic—dealing with the effects of thermal and non-thermal treatments on fruit-based products (beverages and purées) [ 8 , 9 , 10 , 11 , 12 , 13 ]. In the first study, by Zhao et al [ 8 ], the aim was to determine the effect of thermo-sonication combined with nisin and thermal pasteurization treatments on the quality attributes—including microbial and enzyme inactivation and the physicochemical, nutritional, functional, and sensory qualities—of orange juice.…”
mentioning
confidence: 99%
“…Nevertheless, green non-thermal technologies are being widely investigated to reduce costs and make possible more sustainable production processes without affecting the nutritional and sensory quality of beverages. The fourth study, by Salazar-Orbea et al [ 11 ], aimed to discuss the positive and negative effects of thermal treatment and high-pressure processing on the stability of different polyphenol families in agro-food products obtained from strawberry and apple, two of the most-used fruits in food processing. The main findings showed that the phenolic content was affected by the processing, fruit type, polyphenol family, and storage conditions (time and temperature) of the final product.…”
mentioning
confidence: 99%